Relationship between rheological properties of nano polymer modified asphalt binder and permanent deformation of asphalt mixture - Putra Jaya, Ramadhansyah; E., Shaffie; J., Ahmad; A. K., Arshad; N., Mohamad Rais; M. A., Shafii (2011)
Asphalt binder plays an important part in determining many aspects of road performance. However, the rheological properties of asphalt binder are very complex and the parameters depend purely on the viscosity, various loading time and temperature. Therefore, relationship study on asphalt binder rheological properties and asphalt mixture is vital to predict the performance of the mixture. This paper evaluates the relationship between rheological asphalt binder and asphalt mixture performance containing nanopolymer modified binder. Five sets of asphalt binder rheology were tested to determine their viscosity, effect of short term and long term aging using the dynamic shear rheometer (DSR). The asphalt mixtures performance test was then conducted to evaluate the permanent deformation of the mix. Findings from this study indicate that the rheological properties of asphalt binder acts as indicator for the asphalt mixture performance. The G*/sin δ and viscosity of the asphalt binder significantly agree with the resilient modulus and rut depth results obtained. The dependent (resilient modulus at 40oC and rut depth) and dependent (G*/sin δ and viscosity) variables show that these variables significantly affects each other. An effective prediction models can also be developed according to predicted and measured permanent deformation values